Causes of Low Electoral Participation in Iraq: A Field Study from the Perspective of Students at Garmian University - Sameen سامان (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
This study included a sample of (167) students out of 1242 total, and they represented students enrolled in the academic year 2022–2023 spread across the faculties (basic education, agricultural engineering sciences, and the Department of Law) for the fourth stage of study. The study's goal is to examine the causes of Iraq's low voter turnout and the factors influencing it from the perspectives of male and female students at the University of Garmian. The data were described and analysed using the Cronbach's alpha coefficient, percentage, frequencies, arithmetic mean, standard deviation, and sample trend. A stratified random sample method was used, and questionnaires with 38 questions prepared specifically for this purpose were distributed. We were eager to investigate the causes and circumstances of the poor turnout of voters in Iraq's most recent parliamentary elections, which were held on October 10, 2021. The study's findings revealed that respondents' electoral participation is low and their lack of voting in elections is significant. These findings are the result of the interaction of numerous factors, particularly the political and economic ones. The same is true of the influence of social background. It was also clear from the research sample's responses that respondents' confidence in the current state of politics is unstable.